Remediation of Runoff: Options for Container Plant Nurseries - Jyotsna Sharma; P. Chris Wilson; Thomas H. Yeager (EDIS)
ENH-1088, a 6-page illustrated factsheet by J. Sharma, P.C. Wilson, and T.H. Yeager, describes the problem of non-point source pollution from container nurseries, and plant-based and non-plant-based options for remediation. Includes references. Published by UF Department of Environmental Horticulture, January 2008.